2013
DOI: 10.1016/j.bbamcr.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

When ER stress reaches a dead end

Abstract: Endoplasmic reticulum (ER) stress is a common feature of several physiological and pathological conditions affecting the function of the secretory pathway. To restore ER homeostasis, an orchestrated signaling pathway is engaged that is known as the unfolded protein response (UPR). The UPR has a primary function in stress adaptation and cell survival; however, under irreversible ER stress a switch to pro-apoptotic signaling events induces apoptosis of damaged cells. The mechanisms that initiate ER stress-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
297
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(310 citation statements)
references
References 169 publications
12
297
0
1
Order By: Relevance
“…In the present study, we develop evidence that ER stress pathways may be an important regulator of JNK activation in the vasculature in patients with DM by demonstrating increased activation of both the IRE1α and PERK pathways. Prolonged ER stress results in the induction of the pro‐apoptotic transcription factor CHOP, regarded as a key mediator of cell death, endothelial impairment, and disease in response to ER overload 27, 46, 47, 48. In the present study, we showed an enhanced expression of CHOP in the vascular endothelium of patients with DM when compared with controls without DM.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the present study, we develop evidence that ER stress pathways may be an important regulator of JNK activation in the vasculature in patients with DM by demonstrating increased activation of both the IRE1α and PERK pathways. Prolonged ER stress results in the induction of the pro‐apoptotic transcription factor CHOP, regarded as a key mediator of cell death, endothelial impairment, and disease in response to ER overload 27, 46, 47, 48. In the present study, we showed an enhanced expression of CHOP in the vascular endothelium of patients with DM when compared with controls without DM.…”
Section: Discussionsupporting
confidence: 62%
“…Although acute ER stress activation could be beneficial for the cell, chronic ER stress results in an increased translation of ATF4, which promotes the upregulation of genes involved in oxidative stress and apoptosis. Chronic ER stress results in an elevated expression of the pro‐apoptotic transcription factor CHOP 27. Endothelial cells from patients with DM showed higher CHOP expression compared with controls without DM (* P =0.02) (Figure 2), suggesting that DM is associated with a chronic ER stress activation and the activation of apoptotic signaling pathways in the vascular endothelium.…”
Section: Resultsmentioning
confidence: 98%
“…An important feature of apoptosis is the activation of caspases where the Bcl-2 family plays a crucial role in regulating their engagement under ER stress [42]. In our study, we observed that HO-1 induction protected HUVECs against high glucose-induced activation of caspases 3 and 7.…”
Section: Discussionsupporting
confidence: 62%
“…Other examples of crosstalk between trafficking events and apoptosis exist (e.g., ER [147][148][149], Golgi [150]) suggesting that much more is to be uncovered on the reciprocity between apoptosis and intracellular trafficking. For a detailed discussion on organelle remodeling during cell death and crosstalk between organelle status and the apoptotic machinery, see Cheng & Lane [151].…”
Section: Discussionmentioning
confidence: 99%